Nascent technology entrepreneurship among Bulgarian STEM students - Desislava Yordanova (Administrative Sciences, 2021)
Technology entrepreneurship may contribute significantly to economic development and innovation. Little research has investigated the role of the university in technology entrepreneurship among STEM (science, technology, engineering or mathematics) students. More research into the entrepreneurial intentions-behaviour link is needed. This paper aims to identify university-related factors that may contribute to the translation of technopreneurial implementation intentions into actions in a sample of 200 STEM students. The variables university research excellence and perceptions of business development support significantly influence the likelihood of nascent technopreneurial behaviour. This study contributes to a greater understanding of the technopreneurial process and the drivers of technopreneurial behaviour among STEM students. The results of this study may help to enhance nascent entrepreneurship among Bulgarian STEM students.
Keywords: 350; university; nascent technology entrepreneurship; STEM students; student entrepreneurship